Evaluation of competences. Challenges and perspectives from basic to university level - F. Villero, Manuel (2022)
The main purpose of the research was to analyze the evaluation of competencies, challenges and perspectives from the basic to the university level. It was theoretically based on the postulates ofexperts, who from their perspective allow contrasting their different conceptions on the subject in question. Methodologically, it is a study associated with the qualitative exploratory paradigm,under the documentary modality with bibliographic design. Among the most relevant findings of the research, it was revealed that the competency-based curricular approach allows openingroutes to the path of professionalization, from an epistemological and paradigmatic perspective that facilitates the generation of policies and changes in the curriculum design and its implementation, taking into account relevant aspects in the process such as human, material and financial investments of the institutions, being the centerpiece of the curricular approach the graduation profiles, seeking to develop specific and generic skills in students, regardless of the educational level they are studying. A constructivist, contextual, competency-based evaluation approach is proposed, which implies focusing educational praxis on an evaluative model oriented to the processes and steps of the pillars of knowledge based on the integral development of students.